Severe congenital syphilis as cause of unexpected prematurity: 2 case reports and recommended management - Soares Baptista, Sofia; Pereira Coelho, Inês; Tiago, Daniel; Santos, Vera; Soares, Marta; Gaspar, Luisa; Rosa, João (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2023)
Epidemiologic data suggest an increasing incidence of congenital syphilis (CS) in developed countries in recent years. Fetal infection by Treponema pallidum can cause a wide spectrum of clinical manifestations, including stillbirth and prematurity. The physician should always consider infections caused by toxoplasmosis, rubella, cytomegalovirus, herpes simplex virus, and other agents (TORCH) when facing a severely ill preterm neonate. The authors describe 2 very similar cases of severe CS in preterm newborns, both of whom were admitted to the Neonatal Intensive Care Unit. At birth, in addition to severe respiratory distress needing invasive ventilation, the neonates presented with ascites, hepatosplenomegaly, and hydrocele. The preliminary evaluation revealed anemia and thrombocytopenia, which required aggressive transfusion support. Increased inflammatory parameters and cholestasis were also noted. Based on the clinical signs and analytic alterations, TORCH infections were suspected. An investigation was conducted and both neonates had treponemal and non-treponemal positive tests. Both mothers had reactive serologies at the time of delivery, which was previously unknown. Other viral and bacterial infections were excluded. Ultrasonograms of the brains were unremarkable. Ophthalmologic, audiologic, and bone screenings were negative. The neonates received a course of treatment with aqueous crystalline penicillin G for 14 days, and had good outcomes. The diagnosis of CS can be difficult because most infants are asymptomatic at birth and rarely present with severe disease, as shown by our cases. To make a correct diagnosis, it is important to compare treponemal and non-treponemal tests from the mother and newborn because serologies are difficult to interpret. The cases described herein are a reminder of the importance of screening and treatment for these infections during pregnancy and at the time of delivery. It is essential to prioritize health investments in screening programs and to allocate specialized healthcare staff so that syphilis can be treated earlier in the population of reproductive age.